2019
DOI: 10.1038/s41598-019-43428-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel CMKLR1 Inhibitors for Application in Demyelinating Disease

Abstract: Small molecules that disrupt leukocyte trafficking have proven effective in treating patients with multiple sclerosis (MS). We previously reported that chemerin receptor chemokine-like receptor 1 (CMKLR1) is required for maximal clinical and histological experimental autoimmune encephalomyelitis (EAE); and identified CMKLR1 small molecule antagonist 2-(α-naphthoyl) ethyltrimethylammonium iodide (α-NETA) that significantly suppressed disease onset in vivo . Here we directly compared α-NET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Since that previous study, α-NETA has been employed to block the chemerin/CMKLR1 axis in CNS-related diseases, including preeclampsia [ 80 ] and neuroblastoma [ 81 ]. Moreover, α-NETA was reported to be well tolerated in mice [ 82 ]. According to our data, it barely affected the peripheral immune environment in our mouse preclinical GBM models, and α-NETA could precisely target both GBM cells and TAMs owing to the expression pattern of CMKLR1 in GBM tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Since that previous study, α-NETA has been employed to block the chemerin/CMKLR1 axis in CNS-related diseases, including preeclampsia [ 80 ] and neuroblastoma [ 81 ]. Moreover, α-NETA was reported to be well tolerated in mice [ 82 ]. According to our data, it barely affected the peripheral immune environment in our mouse preclinical GBM models, and α-NETA could precisely target both GBM cells and TAMs owing to the expression pattern of CMKLR1 in GBM tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The small molecule 2-( α naphtyl) ethyltrimethylammonium iodide (α-NETA) is a selective CMKLR1 antagonist, which suppresses autoimmune inflammatory response in the central nervous system ( Graham et al, 2014 ). Treatment with α-NETA and α-NETA analogues with structural modifications delay activation of autoimmune encephalomyelitis ( Graham et al, 2014 ; Kumar et al, 2019 ). Interestingly, α-NETA inhibits fat deposition in the liver and adipose tissue as well as lipid accumulation in the liver of high-fat fed mice and suppresses adipocyte gene expression in WAT demonstrating that α-NETA interferes with lipid metabolism ( Xue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…15,52) Some studies suggested that Chemerin treatment inhibited the production of inflammatory cytokines and that this inhibitory effect mainly depended on CMKLR1. [52][53][54] Thus, pretreatment with suitable does of α-NETA, a novel small molecule antagonist of CMKLR1, 36,37) the anti-inflammatory effects of C9 were significantly blocked in Aβ 1-42 induced AD model mice. In BV2 cells, similar to the results of in vivo experiments, after pretreatment with α-NETA, C9 did not inhibit Aβ 1-42 induced inflammatory response.…”
Section: V) On Locomotor Behaviour In Micementioning
confidence: 98%
“…13) Figures 5 and 6 showed the anti-inflammatory effects of C9 in mice. According to Zabel and colleagues reports, 36,37) we synthesized and purified a novel CMKLR1 small molecule antagonist (α-NETA). The synthesis method, mass spectrometry and HPLC analysis of α-NETA are shown in Fig.…”
Section: Icv Administration Of C9 Improves the Object Recognition mentioning
confidence: 99%